EFFECT OF SAPPAN WOOD EXTRACT ON SPERMATOGENESIS AND REACTIVE OXYGEN LEVELS OF ERYTHROCYTE SPECIES OF MALE MICE AFTER EXPOSURE TO CONVENTIONAL CIGARETTE SMOKE - Aras, Fatmawati; Pemayun, Tjok Gde Oka; Winaya, Ida Bagus Oka (Buletin Veteriner Udayana; Vol. 15 No. 2 April 2023DO - 10.24843/bulvet.2023.v15.i02.p10, 2023)
The purpose of this study was to determine the effect of sappan wood extract (Caesalpinia Sappan Linn) on spermatogenesis and reactive oxygen species (ROS) levels of male mice (Mus Musculus) erythrocytes after exposure to conventional cigarette smoke. This study is an experimental study using a completely randomized design (CRD) consisting of control (P0) and three treatments, namely the administration of sappan wood extract (P1) = exposure to cigarette smoke as much as 2 sticks, (P2) = exposure to cigarette smoke 2 sticks and giving sappan wood extract at a dose of 30mg/weight Mice/day, (P3) = Exposure to cigarette smoke 2 sticks and administration of a sappan wood extract at a dose of 60mg/weight mice/day. Experimental animals used in this study were male mice, 6 months old adults and weighing between 20-40 g, totaling 24 individuals. Data analysis for the number of spermatogonia cells, spermatocytes, spermatids and ROS levels of erythrocytes were analyzed using variance if significant changes were found, then Duncan's test was continued. The results showed that the administration of sappan wood extract was able to reduce ROS levels in erythrocytes of male mice after exposure to conventional cigarette smoke, but statistically had no significant effect (P>0.05). Conclusion giving sappan wood extract at a dose of 60mg/weight mice/day gave a more effective effect on the spermatogenesis picture in male mice after exposure to conventional cigarette smoke compared to a dose of 30mg/weight mice/day. Sesuaikan!